Electrical and optical characterization of Mg doping in GaN - Azimah, E.; Zainal, N.; Hassan, Z.; Shuhaimi, A.; Bahrin, A. (Trans Tech Publications, Switzerland, 2013)
Apossible evidence of Mg related emission in Mg doped GaN material is observed inoptical measurement, even without thermal annealing. Meanwhile, the electrical properties of the sample improve when Ni/Au contact layer was annealed up to 400°C, but degrade at further temperature. We propose that such behavior isrelated to degradation of surface morphology of metal contact at higher temperature.